On traitors and heroes: metafictional reflections in a story by Jorge Luis Borges - Trujillo Carrasco, Hagi Harol (2023)
This article contemplates that the story “The theme of the traitor and the hero” by Jorge Luis Borges is a fictional text, since it develops the relationship between reality and fiction, and also, it ponders its own fictional nature. Based on this premise, and taking into account the ideas about art exposed by Oscar Wilde in his essay The decay of lying, an analysis will be carried out. This analysis has an immanent nature and it will focus on the narrative and discursive structures (concepts exposed in the hermeneutical model of Carlos García-Bedoya), using the concepts of plot and fable, narrator, spatialization and temporality. This analysis intends to prove that these syntactic components of the text are specifically related to its metafictional reflection.